Climate Warming Can Accelerate Carbon Fluxes without Changing Soil Carbon Stocks - Ziegler, Susan E.; Benner, Ronald; Billings, Sharon A.; Edwards, Kate A.; Philben, Michael; Zhu, Xinbiao; Laganière, Jerome (Frontiers in Earth Science, 2017)
Climate warming enhances multiple ecosystem C fluxes, but the net impact of changing C fluxes on soil organic carbon (SOC) stocks over decadal to centennial time scales remains unclear. We investigated the effects of climate on C fluxes and soil C stocks using space-for-time substitution along a boreal forest climate gradient encompassing spatially replicated sites at each of three latitudes. All regions had similar SOC concentrations and stocks (5.6 to 6.7 kg C m-2). The three lowest latitude forests exhibited the highest productivity across the transect, with tree biomass:age ratios and litterfall rates 300% and 125% higher than those in the highest latitude forests, respectively. Likewise, higher soil respiration rates ( 55%) and dissolved organic C fluxes ( 300%) were observed in the lowest latitude forests compared to those in the highest latitude forests. The mid-latitude forests exhibited intermediate values for these indices and fluxes. The mean radiocarbon content (∆14C) of mineral-associated SOC (+9.6 ‰) was highest in the lowest latitude forests, indicating a more rapid turnover of soil C compared to the mid- and highest latitude soils (∆14C of -35 and -30 ‰, respectively). Indicators of the extent of soil organic matter decomposition, including C:N, δ13C, and amino acid and alkyl-C:O-alkyl-C indices, revealed highly decomposed material across all regions. These data indicate that the lowest latitude forests experience accelerated C fluxes that maintain relatively young but highly decomposed SOC. Collectively, these observations of within-biome soil C responses to climate demonstrate that the enhanced rates of SOC loss that typically occur with warming can be balanced by enhanced rates of C inputs.